(untitled) (Contemporary Journal of Social Science Review, 2025)
This paper focuses on the concept that multilingual people vie and negotiate identity in terms of language in home, institutional (education/workplace), and digital contexts. We employed the mixed-methods design to survey 200 individuals and conducted 24 semi-structured interviews and used 36 hours of natural interaction recordings, complemented by the surveys. Quantitative results showed perceived linguistic legitimacy to be the most predictive predictor of belonging but ideological pressure (e.g., standard-language demands and accent bias) had negative predictive power of both predictors and belonging. Flexibility with repertoes exhibited independent positive relationships with belonging indicating that availability and trust in an extensive communicative repertoire can be used to promote inclusion when it is socially accepted. The mixed-repertoire use was found to be higher at home and online, as compared to the formal institutional settings where the individuals expressed that they had increased self-monitoring. The qualitative themes helped explain how these patterns were achieved: speakers employed translanguaging and code-switching to fit in groups, control impressions and display hybrid identities, and balance between legitimate identity performance, which limited the performance of acceptable identities. In general, the results put identity negotiation in a more situated, power-infused, and interactionally driven dynamic influenced by the broader language ideologies, and with practical consequences of more inclusive educational and workplace language policies. Our suggestions are institutional practices that limit the gatekeeping, importance to multilingual repertoires, and monitoring identity change over time in offline-online conditions